Organocatalytic cascade knoevenagel-michael addition reactions: direct synthesis of polysubstituted 2-amino-4H-chromene derivatives - Jadhav, Sanjay N.; Patil, Seema P.; Sahoo, Dipti Prava; Rath, Dharitri; Parida, Kulamani; Rode, Chandrashekhar V. (Catalysis Letters, 2020)
In this report, we documented novel strategy for the synthesis of bioactive polysubstituted 2-amino-4H-chromine derivatives under a heterogeneous Al-MCM-41-LDH@APTES (ALAM) catalysis. A synthetic procedure is developed to prepare Al-MCM-41-LDH@APTES (ALAM) heterogeneous basic catalysts. Mesoporous Al-MCM-41 is functionalized by known grafting chemistry via layered double hydroxide (LDH) nanosheets and (3-aminopropyl)triethoxysilane (APTES) moiety as a basic organocatalyst. The resulting catalysts contain amino group functionality on the external surface as well as inside the layers and the basicity can be tuned by the loading of APTES. The samples were fully characterized by Si-29 and C-13 CP/MAS NMR, infrared absorption spectroscopy, TEM, XPS, EDX, TGA, XRD, CO2-TPD, N-2 adsorption isotherms measurements, and they were successfully examined for the cascade type Knoevenagel-Michael addition reactions. The product yields associated with these substrates were optimized, and key reaction parameters affecting the yields were identified. The present catalytic method is simple and robust for diversity oriented synthesis which proceeds good to excellent yields without generating any hazards waste. The broad substrate scope, excellent functional group compatibility makes this protocol highly useful towards synthesis of polysubstituted alpha-cyanoacrylates, alpha-cyanoacrylonitriles and 2-amino-4H-chromenes with an electron-donating or electron-withdrawing group. We have also successfully established a flow reaction system, gram-scale synthesis as well as catalyst recyclability up to six catalytic cycles without appreciable loss of its activity. Graphic
Keywords: 2-Amino-4H-chromines; Amine functionalized solid catalysts; cascade synthesis; Diversity oriented syntheses (DOS); flow chemistry

Prominence of Cu in a plasmonic Cu-Ag alloy decorated SiO2@S-doped C3N4 core-shell nanostructured photocatalyst towards enhanced visible light activity - Babu, Pradeepta; Dash, Soumya Ranjan; Behera, Arjun; Vijayaraghavan, T.; Ashok, Anuradha; Parida, Kulamani (Nanoscale Advances, 2021)
A series of Cu-Ag bimetal alloys decorated on SiO2 and the fabrication of few-layer S-doped graphitic carbon nitride (SC) warped over it to form a core-shell nanostructured morphology have been demonstrated and well characterized through various physiochemical techniques. HRTEM data confirmed the formation of a compact nanojunction between the SiO2 and SC, where Cu-Ag is embedded uniformly with an average particle size of 1.3 nm. The Ag : Cu (1 : 3) between SiO2 and SC produces 1730 mu mol h(-1) g(-1) of H-2 under visible light illumination. Moreover, 6.2-fold current enhancement in the case of Ag : Cu (1 : 3) as compared to the Ag-loaded core-shell nanostructured photocatalyst indicates higher electron-hole-pair separation. The excellent activity was due to the synergistic alloying and plasmonic effect of Ag and Cu. DFT studies reveal that the Cu atom in the Cu-Ag bimetal alloy plays a pivotal role in the generation of H-2, and the reaction proceeds via a 4-membered transition state. The mechanistic insight proceeds from the generation of hot electrons due to the LSPR effect and their transfer to the SC layer via a compact nanojunction.

Facile fabrication of nano silver phosphate on B-doped g-C3N4: an excellent p-n heterojunction photocatalyst towards water oxidation and Cr (VI) reduction - Sahoo, Mitarani; Babu, Pradeepta; Singh, Chandrodai Pratap; Krishnamurty, Sailaja; Parida, Kulamani (Journal of Alloys and Compounds, 2022)
A photostable Ag3PO4/BCN type-II p-n heterojunction has been demonstrated by loading nano Ag3PO4 on B-doped g-C3N4 nanosheet (BCN). The photocatalysts were successfully characterized by various physicochemical techniques and their photocatalytic activities were tested towards the water oxidation reaction to produce oxygen and Cr (VI) reduction under visible light. The HRTEM confirms Ag3PO4 with a particle size of 15 nm has been deposited on BCN to construct a p-n heterojunction. The BCNS-50 absorbs more visible light in the solar spectrum as compared to other catalyst, demonstrating the ability to generate 587 mu mol h(-1)g(-1) O-2 and reduces 98% of 20 ppm Cr (VI) solution in 1 h. The lower PL intensity as well as lower arc value in case of BCNS-50 suggests the maximum e-h separation and lower charge transfer resistance across the semiconductor/electrolyte interface. The BCN sheet provides a compact heterojunction where the oxidation peak of Ag3PO4 decreases gradually and disappear in case of BCNS-50 suggesting the enhance stability of Ag3PO4 in the heterojunction. BCNS-50 could able to produce -139 and 3087.5 mu A photocurrent both in cathodic and anodic direction which is approximately 7 and 2.4 folds higher as compared to nano Ag3PO4. The generation of photocurrent in both cathodic and anodic direction confirms the formation of p-n heterojunction which further supported by Mott-Schottky analysis. Furthermore the construction of the p-n heterojunction is verified via Mott-Schottky study. DFT calculation explains the contribution of various atomic orbital of Ag3PO4 and BCN towards the formation of hybrid orbital in the heterojunction and the path for charge delocalization between them. This work may provide a limelight and alternative pathway for enhanced photocatalytic performance on construction of the p-n heterojunction in a simple way. (C) 2021 Elsevier B.V. All rights reserved.
Keywords: Cr (VI) reduction; Density functional theory; Interfacial zone; p-n heterojunction; Photocatalyst; Water oxidation

Mechanistic insight the visible light driven hydrogen generation by plasmonic Au-Cu alloy mounted on TiO2 @B-doped g-C3N4 heterojunction photocatalyst - Babu, Pradeepta; Dash, Soumya Ranjan; Parida, Kulamani (Journal of Alloys and Compounds, 2022)
Designing of two dimensional surfaces and interfaces with light-active materials has been established as a versatile approach to increase their photocatalytic activity. In the present work, n-type anatase TiO2 coupled with p-type B-doped g-C3N4 nanosheet (BCN) were fabricated and Au-Cu nanoalloy with varying atomic ratio were deposited on the p-n heterojunction. The incorporation of Au-Cu on the interface of the dyad enhances light absorption over broad regime, charge separation, and migration. Au-Cu with 1:1 ratio (with an average particle size of 1.2 nm) loaded p-n hetrojunction (TBCAC-1:1) shows excellent photocurrent enhancement (approximately 4.4-folds) in the cathodic direction as compared to their monometallic plasmonic counterpart. Additionally, the catalyst shows photocurrent at zero biased potential as well as lower onset potential as compared to the other alloy. TBCAC-1:1 photocatalyst could able to produce 2150 mu mol h(-1)g(-1) of hydrogen, which is (approximately 3-folds) as compared to their monometallic counterparts. The hydrogen evolution process for Au-Cu (1:1) system was found to be governed by the charge distribution which dictates the binding preference of the Au and Cu sites leading to the water splitting as investigated by DFT calculation. The excellent hydrogen generation by the photocatalyst links to the synergistic effect between Au and Cu associated with the hot electron photochemistry due to surface plasmon resonance phenomenon. (C) 2022 Published by Elsevier B.V.
Keywords: Doped carbon nitride; hydrogen production; LSPR; P-n junction; Photocatalysis; Plasmonic alloy